2019
DOI: 10.1002/vms3.194
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antimicrobial‐resistant Escherichia coli in endangered Okinawa rail (Gallirallus okinawae) inhabiting areas around a livestock farm

Abstract: Antimicrobial resistance (AMR) is an important issue for public, animal and environmental health. It has been suggested that livestock farms could be a source origin of AMR, and some wild animals that inhabit this area may play an important role in the spread of AMR in the natural environment. The prevalence of AMR in Escherichia coli was examined from Okinawa rails (Gallirallus okinawae), an endemic bird in Okinawa Main Island, Japan. Forty‐eight faecal samples of wild Okinawa rails were collected from around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Rolland et al [42] compared the prevalence of AMR in groups of wild baboons (Papio cynocephalus) in Amboseli National Park, Kenya, finding low prevalence in those with little to no contact with humans, while 94.1% of samples from those close to a tourist lodge and its associated human waste carried multiple resistances. Livestock have been linked to a higher prevalence of AMR in proximate wild animals, including migratory birds and small mammals in several studies [37,38,[43][44][45][46][47]. AMR E. coli prevalence was very high (71.43%) in Egyptian vultures (Neophron percnopterus) wintering at a livestock carcass dump in India [40].…”
Section: (B) Amr Escherichia Coli In Wild Animalsmentioning
confidence: 99%
“…Rolland et al [42] compared the prevalence of AMR in groups of wild baboons (Papio cynocephalus) in Amboseli National Park, Kenya, finding low prevalence in those with little to no contact with humans, while 94.1% of samples from those close to a tourist lodge and its associated human waste carried multiple resistances. Livestock have been linked to a higher prevalence of AMR in proximate wild animals, including migratory birds and small mammals in several studies [37,38,[43][44][45][46][47]. AMR E. coli prevalence was very high (71.43%) in Egyptian vultures (Neophron percnopterus) wintering at a livestock carcass dump in India [40].…”
Section: (B) Amr Escherichia Coli In Wild Animalsmentioning
confidence: 99%
“…On the other hand, in the isolates from mammals of animal facilities, high resistance rates were observed for AMP (23.6%), SXT (18.9%), TET (17.9%), and NAL (11.3%) ( Table 1). Along the Okinawa rail between farm and forest areas, the birds in the farm area were more frequent carriers of AMR E. coli (69%, 11/16) compared to those in the forest area (20%, 3/15) [10]. Usui et al suggested that flies in animal farms may carry and spread antimicrobial-resistant bacteria of reared animals [27].…”
mentioning
confidence: 99%
“…In our previous study, we isolated ARG-coding E. coli ( bla CTX-M1 -harboring E. coli ) from a rat captured on a farm; a similar ARB was isolated from egg-laying hens on the same farm [ 3 ]. A survey of Okinawa rail, a protected species, also reported a high rate of ARB isolated from individuals in the vicinity of a farm [ 33 ]. The bla CTX-M-14 plasmid was found to be transmitted between farm animals and weasels captured around animal facilities [ 84 ].…”
Section: Wildlifementioning
confidence: 99%